Biochanin A Has Protective and Therapeutic Effects against Li2CO3-induced Nephrotoxicity in Rats Model - Alamri, Zaenah Zuhair; Alfaifi, Soliman Mohammed (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Long-term usage of lithium carbonate (Li2CO3) as treatment of bipolar disorder might cause nephrotoxicity. Li2CO3-induced nephrotoxicity usually treated by renal dialysis, which is quite expensive. Usage of natural products that possess anti-inflammatory and antioxidant properties as biochanin A (BCA) may be useful against Li2CO3 nephrotoxicity. Therefore, this study was conducted to evaluate Li2CO3 nephrotoxic effects and BCA therapeutic and protective effects against it.METHODS: Twenty-eight rats divided into 4 groups: negative control (NC), Li2CO3, Li2CO3 + BCA therapeutic, and BCA + Li2CO3 protective group. Complete blood picture, serum kidney function tests (urea, creatinine, and cystatin C) and kidney tissue homogenate oxidative stress index as malonaldehyde (MDA), superoxide dismutase (SOD), glutathione S-transferase (GST) and catalase (CAT) were measured using enzyme linked immunosorbent assay (ELISA) methods. While, kidney histopathological changes were evaluated under light microscope.RESULTS: Li2CO3 administration elicited significant changes in hematological parameters as hypochromic anemia, decreased platelets and leukocytosis. Serum urea, creatinine and cystatin C were elevated. Renal homogenate analysis revealed significant elevation of MDA and decline in GST, CAT, SOD levels. Kidney histopathology analysis revealed hemorrhage between renal tubules, glomerular capillaries congestion, Bowman’s space dilatation, structural alterations in renal tubules cells include loss of brush border, deeply stained nuclei and elevated in size and number of cytoplasmic vacuoles. Therapeutic and protective groups of BCA showed amelioration of hematological alteration, kidney functions, oxidative stress markers and restoration of kidney tissues.CONCLUSION: BCA has both protective and therapeutic effects against Li2CO3-induced nephrotoxicity possibly through the reduction of oxidative stress.KEYWORDS: biochanin A, hematological changes, kidney, lithium carbonate salt, oxidative stress, protective effects, therapeutic effects